(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The first six to eight years of a child’s life are the most crucial in their development!! Because of the rapid pace of growth throughout these years, the early childhood era is typically considered as the most critical for life-long development. "Experience-based brain development in the early years develops neurological and molecular pathways that impact health, learning, and behavior throughout life," according to recent neuroscience studies. These early years of life are critical for the development of numerous cognitive, social, and psychomotor abilities that contribute significantly to later life success. If a stimulating and enriching physical and psychological environment is not provided during these critical ages, the chances of the child’s brain developing to its full potential are considerably reduced, and sometimes permanently. According to the conclusions of this research, a considerable number of poor children, particularly in developing nations, are "at risk" in terms of their future chances. “In many nations, disadvantaged children have a significant cognitive and social disadvantage by the time they reach school age.